2019
DOI: 10.1021/acs.iecr.9b06542
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Solubility of Oxides of Metals and Metalloids in Supercritical Water

Abstract: The solubility of oxides of metals and metalloids in water can be considered as a reaction of hydration with the formation of hydroxides species, like Al(OH) 3 •H 2 O, Si(OH) 4 , B(OH) 3 , etc. Calculation of solubility requires, along with the equilibrium constant of the dissolution reaction in the ideal gas state, knowledge of the fugacity coefficients, φ 2 ∞ , for aqueous species. This work describes simple ways of estimating fugacity coefficients for such species in water of various pressures/densities, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…The current study uses methods of evaluation of solubility of oxides in water with the formation of hydroxides based on thermodynamics of nonideal fluid mixtures, as advocated earlier. 27 The essential points are the estimation of the fugacity coefficients of the silica monomer and the dimer, Si(OH) 4 and Si 2 O(OH) 6 , and computation with the quantum chemistry (QC) methods of the thermodynamic properties of these species in the ideal gas state. Like Gerya et al, 26 we found that to match the speciation data for aqueous silica at high temperatures, we have to consider the polymerization of silica beyond the dimer.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…The current study uses methods of evaluation of solubility of oxides in water with the formation of hydroxides based on thermodynamics of nonideal fluid mixtures, as advocated earlier. 27 The essential points are the estimation of the fugacity coefficients of the silica monomer and the dimer, Si(OH) 4 and Si 2 O(OH) 6 , and computation with the quantum chemistry (QC) methods of the thermodynamic properties of these species in the ideal gas state. Like Gerya et al, 26 we found that to match the speciation data for aqueous silica at high temperatures, we have to consider the polymerization of silica beyond the dimer.…”
Section: Introductionmentioning
confidence: 63%
“…The thermodynamic properties of pure water throughout this work are calculated from the Wagner−Pruß equation of state. 29 The second approach, the density model, is consistent 27 with the following expression for A 12…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations